2020
DOI: 10.4136/ambi-agua.2551
|View full text |Cite
|
Sign up to set email alerts
|

Food ecology and presence of microplastic in the stomach content of neotropical fish in an urban river of the upper Paraná River Basin

Abstract: Plastic is a useful material; but along with its benefits also come several disadvantages. One of these is the consequences of the improper discarding of plastic in the environment and its eventual fragmentation into microplastics. Plastic can reach rivers and affect their biota as microparticles from its degradation. The entry of plastic into the food chain occurs by the consumption of fish or other organisms. Furthermore, persistent organic pollutants can accumulate, and the consumption of materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The diet of the native species H. littorrale in a lentic environment reflected and corroborated the influences of the environment on the fish diet. Studies in a lotic environment have demonstrated iliophagous (Oliveira et al, 2020) and omnivore-planktivore feeding habits for the species (Caldeira et al, 2007;López-Rodríguez et al, 2019). However, here, the species demonstrated detritivore feeding habits with the consumption of detritus and aquatic insects in both lagoons, confirming this species' opportunism and trophic plasticity.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The diet of the native species H. littorrale in a lentic environment reflected and corroborated the influences of the environment on the fish diet. Studies in a lotic environment have demonstrated iliophagous (Oliveira et al, 2020) and omnivore-planktivore feeding habits for the species (Caldeira et al, 2007;López-Rodríguez et al, 2019). However, here, the species demonstrated detritivore feeding habits with the consumption of detritus and aquatic insects in both lagoons, confirming this species' opportunism and trophic plasticity.…”
Section: Discussionsupporting
confidence: 65%
“…In other studies, H. littorale has shown to be omnivorous (Caldeira et al, 2007;López-Rodríguez et al, 2019), invertivores (Santos, Ferreira, & Amadio, 2008) and planktivorous (Echevarría, Rodríguez, & Machado-Allison, 2018;López-Rodríguez et al, 2019). However, most of the work carried out with the species has been in rivers (Caldeira et al, 2007;López-Rodríguez et al, 2019;Oliveira, Corrêa, & Smith, 2020), with little information on its biological aspects (diet and feeding habits) in lentic environments, e.g., lagoons. Lentic environments are characterized as having water that is almost still or with variable flows (lakes, lagoons, dams, reservoirs), low current strength, and with mainly autochthonous energy (Oliveira & Goulart, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Most of the species that consumed human debris, with the exception of Trachelyopterus striatulus, are non-native to the Rio Doce basin (sensu Vieira 2010, Jégu 2003. Studies published (e.g., Ribeiro-Brasil et al 2020, Garcia et al 2020, Oliveira et al 2020, Oliveira et al 2021 show that numerous native freshwater fishes of the ecosystems are able of consuming plastics and other objects of human origin. Thus, we believe that other native species of the Rio Doce -besides T. striatulus -are also consuming anthropogenic materials.…”
Section: Discussionmentioning
confidence: 99%